2023
DOI: 10.1002/sys.21714
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the digital transformation maturity level independently with the design science research methodology

Tining Haryanti,
Nur Aini Rakhmawati,
Apol Pribadi Subriadi

Abstract: This study uses the Design Science Research Methodology (DSRM) approach in creating an artifact on the perspective of the Information System. Design Science as a valuable tool for creating a new artifact or developing an existing artifact through research. The DSRM Framework described in this study discusses the implementation of each stage, namely, Explicated Problem, Define Requirement, Design and Development, Demonstration, and Evaluation and is complemented by the implementation of case studies of artifact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Within DSR, Design Science Research Methodology (DSRM) occurs using the principles or guidelines associated with this paradigm [37]. There have been various attempts to formalize methodology [38,39], though it differs across disciplines [40][41][42]. For example, within Information Systems Research, Peffers et al (2007) [39] defined the Design Science Research Methodology (DSRM) as a six-activity process, as shown in Figure 1 and summarized as follows [43]:…”
mentioning
confidence: 99%
“…Within DSR, Design Science Research Methodology (DSRM) occurs using the principles or guidelines associated with this paradigm [37]. There have been various attempts to formalize methodology [38,39], though it differs across disciplines [40][41][42]. For example, within Information Systems Research, Peffers et al (2007) [39] defined the Design Science Research Methodology (DSRM) as a six-activity process, as shown in Figure 1 and summarized as follows [43]:…”
mentioning
confidence: 99%